The Electrical Characteristics of Fruit Peel Waste as a Biobattery in Terms of Fermentation Time and Coconut (Cocos nucifera L.) Pulp Concentration - Siti Fatimah; Putut Marwoto; Sunyoto Eko Nugroho (Jurnal Penelitian Pendidikan IPA, 2023)
Bioenergy is an alternative energy that utilizes various types of organic waste that can generate electricity. The purpose of this study was to determine the effect of fermentation time and coconut pulp concentration on the electrical characteristics of durian fruit skin, banana fruit skin, and cassava skin waste as an alternative energy source. The electrical characteristics observed were the voltage generated by fruit peel waste based on fermentation time and coconut pulp concentration. This research is a laboratory-based experimental research. The results of the study showed that: 1) the length of fermentation time affects the voltage generated by durian skin, banana skin, and cassava skin; 2) the fermentation time to produce the best voltage is the fourth day (96 hours); 3) the longer the fermentation time, the lower the voltage generated; 4) coconut pulp concentration affects the voltage generated by durian skin, banana skin, and cassava skin; 5) the ratio of 25% coconut pulp concentration and 75% raw material concentration becomes the ratio that produces the best voltage; 6) durian fruit peel waste has the highest voltage compared to banana fruit peel and cassava peel waste, both in terms of fermentation time or coconut pulp concentration. 7) cassava peel waste has a higher potential difference resistance than other skin waste